(3eYGfj GdbQBf hEYQGHgs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3MOKfG GHh eMeO YHO Gddg Hf eMeO Hf bGSe Hf MRe Hf GdMSf GdVQjQ bGd bGd GHh GSMGb GdRLGL HSe Gddg GdLGdH eYfi GdGHJOGA cCfc bdJ HOCJ HGSe Gddg s
(3BNQgG (B:s
(3hgPG GdeYfi CeQ GdOYGA Efg jSJYGP ef TQ GdLf hGdGfS hOdjd Pdc ef TQ eG Ndb s
(3fSNI fajSIs
(3jdi Pdc GdcJGH ahGFO JJYdb HHYV GdeSGFd GdJi hQOJ ai GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
Keywords: (3GdfMhs